Paths to globalization: Korean chaebol and Chinese SOEs - Johnson, James P. (Henry Stewart Talks, 2013)
Globalization, South Korea, China, Economic development, State-owned enterprises (SOEs), Chaebol, Resource based view, Institutional theory, Hofstede’s dimensions of culture, Cultural values, In-mak, Guanxi, Export led industrialization, Structural reforms